Knowledge in Memory Evolutive Systems - Ehresmann, Andree C.; Vanbremeer, Jean-Paul (Theoria et Historia Scientiarum, 2007)
The Memory Evolutive Systems (MES), introduced in a series of former papers, propose a mathematical model, based on Category theory, for open autonomous hierarchical systems such as biological, neural or social systems. Here the authors show that MES give a framework in which to study the formation, representation and interpretation of knowledge. In particular, they explain how the system can acquire pragmatic or conceptual knowledge though the coordinated action of a net of competitive internal patterns of agents, called coregulators (or CRs). This knowledge is not rigid, but is adapted to different situations subject to an appropriate choice of some parameters. Depending on its complexity level, a CR participates in an automatic or deliberate manner to the development of the collective distributed memory, relying on the partial information it collects at its own timescale on the system, its environment and the records of its past experiences. Higher CRs can classify records and develop more complex conceptual knowledge. Language (for men and social groups allows a system to interpret its own knowledge and intentionally diffuse it.